Integrated Miniature Multiband Antenna Designed for WWD and SAR Assessment for Human Exposure - Brahim Fady; Jaouad Terhzaz; Abdelwahed Tribak; Fatima Riouch (International Journal of Antennas and Propagation)
The article introduces a new, low-cost, integrated, multiband antenna design intended for wristbands and wearable wireless devices (WWD). With a miniaturized planar square-shape sizing 29 × 29 mm2, the antenna can fit easily inside WWDs. The proposed design covers the most used frequency bands such as LTE2300, ISM2400, LTE2600, WiMAX3500, WiMAX5200, and ISM5800 in which the antenna reaches up to −25 dB and 6.9 dBi in terms of S11 and gain, respectively. To evaluate the exposure amenability of design on human body, we studied the specific absorption rate (SAR) of the design in two main use cases: multilayered human wrist model and a SAM (Specific Anthropomorphic Mannequin) head model. In each use case, the SAR results in different positions for all frequencies are compared to FCC standards.